Uso do jogo “marinheiros do espaço” como ferramenta pedagógica nas aulas de astronomia do ensino medio - Costa Júnior, Francisco Vanderley (Universidade Federal Rural do Semi-Árido, 2019)
This work is the result of the application of the RPG (Roleplaying Game), Space Sailors, as a pedagogical tool in physics classes related to astronomy. The game was applied to a senior year class in a private high school in the city of Aracati /CE, Brazil. The objective was to analyze how RPG can help the teaching-learning process in physics, bringing to students, in a playful way, a different and pleasant way of interacting with presented concepts. To culminate with the application of the product itself, we had to have four meetings so that students could have access to a process of building concepts that would be necessary in the adventure. The theoretical foundation was based on Vygotsky's SocioConstructivist Theory. At the end of the application of our work, we noticed a positive result related to the assimilation of the physical concepts presented in the game. The use of this resource also promoted a greater interaction between students before, during and after its application.
Keywords: Ferramenta Pedagógica; Forma Lúdica; Ensino-aprendizagem; Pedagogical tool; Ludicity; Teaching learning process; CIENCIAS EXATAS E DA TERRA::FISICA